Law Enforcement Against Slavery of Indonesian Crews on Foreign Fishing Vessels - Yunandar A. Supu (Estudiante Law Journal, 2019)
Abstract: This study aims to find out about law enforcement against the slavery of Indonesian crew members on foreign fishing vessels. The method used in this research is a type of normative research that uses a law approach and case studies. The results of this study indicate that international law enforcement related to slavery on foreign fishing vessels against Indonesian crew members has been stated in the Universal Declaration of Human Rights, Convention Against Torture and Other Cruel, In Human or Degrading Treatment or Punishment, Convention on The Elimination. of All Forms Of Racial Discrimination, in Fishing Convention, 2007 (No. 188). It is undeniable that these various legal instruments can protect Indonesian crew members who work outside the jurisdiction of Indonesia because the regulations contained therein, such as the ILO Convention Number 188 of 2007 contain requirements for ship conditions, accommodation, and food, safety, and health. employment, health services, and social security.